Design and architecture of a novel preservation watch system - Faria, Luís (2012)
Successful preservation of content requires sophisticated mechanisms for collecting, tracking and analyzing information about a multitude of relevant aspects. This is not limited to content itself, but also tracking of available software, other organization’s content, usage statistics and trends, format risks, systems operations and many more. Such tracking requires a flexible system that supports evolution over time and provides an extensible platform for scalability. This article presents a novel approach towards automated monitoring of preservation-related information. We discuss the challenges and information sources that need to be covered and outline the key design features of a novel preservation watch system. We discuss how this system addresses critical information needs for informed preservation management and outline next steps ahead.